Identifying instructional mediation patterns related with progress in reading comprehension in contexts of sociocultural disadvantage - Mardones, Tricia; Navarro, Juan-José; Zamorano, Leandro (Anales de Psicología / Annals of Psychology, 2020)
Identifying specific instructional factors related to progress in reading comprehension is essential to optimize learning and guide intervention, especially in contexts of sociocultural disadvantage or learning difficulties. This study aims to identify effective mediational instructional patterns in the explanation of progress in reading comprehension. Teaching guidelines were systematically recorded in relation to different reading processes. Eighty-two sessions were recorded, transcribed and analyzed by coding and categorizing the content of the sessions through the Maxqdea-7 program. Nineteen categories were considered, which comprised 178 significant units of information (mediation guidelines). The sample consisted of 21 teachers and 821 students from third to the eighth grade of public schools of Chile located in deprived contexts. Reading progress was measured with the standardized CL-PT test, which was applied at the beginning and end of the school year. The results have allowed identifying mediation patterns with a significant relevance in the explanation of reading progress, especially the pattern M_P17 (Mediation of the use of strategies for the activation and integration of previous knowledge) managed to explain 26% of the variance in the progress (r = .55, p < .01; R2adjusted = .26, F(1, 19) = 8.19, p = .01). The educational implications of these results are discussed.